STRUCTURAL DAMAGE IDENTIFICATION BASED ON EEMD AND NORMALIZED ENERGY DIFFERENCE OF IMF - JI QunCe; HE XiaoHui; ZHANG MeiJun; ZHANG Yu (Jixie qiangdu)
Aiming at the problem that the influence of environmental factors and insensitive damage indicators make structural damage identification difficult,a new method of structural damage identification based on EEMD and normalized energy difference of IMF was proposed. First,a group of IMF components of original signal was obtained by EEMD. The energy of IMF components of each measured point was calculated and normalized,The difference between the normalized energy of IMF components before and after damage was obtained. The change curve of each state was constructed by using the difference as the structural damage indicator and conclude the damage location and degree through comparing before and after structural damage.Finally,a series of the experimental data from a three-story building structure and simply supported beam were analyzed to validate the viewpoints in this paper. Results indicate that the method is effective.